ANALISIS PROFITABILITAS DAN RASIO AKTIVITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Itsniani, Fitria Senjaning; Husda, Anggun Permata (LPPM Universitas Putera Batam, 2022)
This study aims to determine the analysis of profitability and the ratio of activity to the value manufacturing companies in the food and beverage listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 periods. The population of this study was selected using purposive sampling method based on predetermined criteria 10 samples of manufacturing companies were taken selected as a sample.. The method of analysis was carried out using multiple linear regressions analysis and the applicationinstrument the SPPS (Statistical Product and Services Solutions). The result of this study simultaneously state that Profitability and Activity Ratios have no significant effect on firm value.